Crisis of Dominance: Understanding the Rural–Urban Roots of Maratha Caste Mobilisation for Reservation. (May 2021) - Mhaskar, Sumeet
The post-liberalisation era in India has witnessed mobilisations among socially superior castes for reservation/affirmative action. I examine why Marathas have intensified their mobilisation in the past few years by using qualitative and quantitative data gathered over a period of 14 months in 2008–2009 and several visits during 2010–2019 in Mumbai and Maharashtra. I argue that a crisis of dominance explains the Maratha's mobilisation for reservation. Understanding this crisis involves paying attention to the link between two crises—'urban' and 'rural'. The former arises from the rapid disappearance of well-paid jobs since the late 1990s in large-scale manufacturing and other industries in urban areas. The latter refers to the return of retrenched factory workers to their villages and the loss of their social status. It also refers to the inability of the rural youths with low or vernacular education to migrate to urban areas for well-paid employment, and the disturbance of caste hierarchy norms in rural settings. I conclude that the Maratha crisis of dominance will persist under the neoliberal Indian state due to the privatisation of higher education and absence of well-paid, secured jobs for individuals with low level or vernacular education. The price of this crisis will be paid by Dalits, who have been the victims of brutal atrocities carried out by the Marathas.